EFFECT SURFACE NITRIDING TREATMENT ON INTERFACE ADHESION AND SURFACE DAMAGE OF CL60 RAILWAY WHEELS UNDER ROLLING CONTACT CONDITIONS - WU Qiang; QIN Tao; SHEN MingXue; XIONG Wei; PENG JinFang; JI DeHui; XIONG GuangYao (Jixie qiangdu)
The influence of nitriding treatment on wheel/rail rolling contact fatigue and surface wear behavior of CL60 wheel was studied on JD-DRCF/M rolling contact fatigue/wear tester,the wheel surface nitriding treatment on the mechanisms of wheel/rail surface damage are compared and analyzed. The results showed that the surface nitriding treatment could form a uniform and dense white layer about 3 μm ～ 5 μm thick and a diffusion layer about 20 μm thick on the wheel surface. Under the wheel surface after nitriding process,the adhesive coefficient between wheel/rail was reduced by 11. 7% in dry condition,and reduced by 18. 4% in aqueous media,but the nitriding treatment still can keep the higher adhesive coefficient between wheel/rail system,which can prevent the occurrence of the phenomenon such as wheel-slip; Nitriding treatment not only significantly improve the wear resistance on the surface of the wheel,but also effectively reduce the wear of the rail sample,the amount of damage reduced by 58. 05% and 10. 77%,respectively. In short,the nitriding on wheel for wheel/rail system can effectively reduce the wear,improve the rolling contact fatigue resistance of wheel materials. The method is applied to the actual,it can effectively improve the service life of wheel/rail system,reduce the damage of wheel/rail material under the heavy-load condition.